Penerapan Rehabilitasi Sosial bagi Penyalahguna Narkotika: Studi di Lembaga Pemasyarakatan Narkotika Kelas IIA Kabupaten Bangli - Sijabat, Josephine Yenni; Hartono, Made Sugi; Wayan Yasmiati, Ni Luh (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the implementation of social rehabilitation for drug abusers in the Class IIA Narcotics Correctional Institution, Bangli Regency. The research background stems from the need to understand how social rehabilitation is implemented within the correctional system, considering that drug abusers require not only legal guidance but also physical, mental, and social recovery to return to optimal functioning in society. This study employed an empirical research method with a qualitative approach. Data collection included field observations, interviews with correctional officers, addiction counselors, and inmates, and document analysis related to the implementation of the rehabilitation program. This research also focused on understanding how social rehabilitation is designed to support the recovery of drug abuse inmates and how it aligns with applicable regulations within the correctional system and drug prevention policies. The results of this analysis are expected to contribute to the development of social rehabilitation concepts and practices in correctional settings, as well as provide input for relevant parties in improving the quality of rehabilitation services for drug abusers.